Comparison of the analgesic effects of oxycodone vs. sufentanil on postoperative pain after laparoscopic gallbladder-preserving cholecystolithotomy: a prospective randomized controlled trial - Wang, Ye; Wu, Meng; Zhao, Lin; Yan, Xiaojian; Zhao, Lei (Frontiers in Surgery, 2024)
We aimed to compare the anesthesia induction effects of oxycodone and sufentanil on postoperative pain in patients undergoing laparoscopic gallbladderpreserving cholecystolithotomy, as well as changes in serum levels of inflammatory factors (TNF-α, IL-6, and IL-10) in the perioperative period.Methods: Sixty patients who underwent laparoscopic gallbladder-preserving cholecystolithotomy were evenly divided into oxycodone (O) and sufentanil (S) groups. In groups O and S, oxycodone (0.3 mg/kg) and sufentanil (0.3 ug/kg) were administered, respectively, followed by propofol (2 mg/kg) and rocuronium (0.6 mg/kg). In both groups, the intraoperative electroencephalography double-frequency index was used to guide the use of sedative and analgesic drugs, assessing the followup analgesic effect (VAS), degree of sedation (Ramsey), and postoperative complications at seven different time points (0, 0.5, 2, 4, 6, 8, and 24 h postoperatively).Results: Compared with the S group, patients in the O group exhibited lower VAS scores within 24 h postoperatively (P < 0.001), but there was no statistical difference between wound and shoulder pain scores (P > 0.05). Regarding postoperative awakening and extubation duration, O group patients experienced shorter times and better remedial analgesia (P <0.05). In terms of the degree of sedation, the Ramsay score decreased at 0 h postoperatively compared with the S group (P <0.001).Compared with sufentanil, oxycodone anesthesia induced better postoperative analgesia and less inflammatory responses in patients undergoing laparoscopic gallbladder-preserving cholecystolithotomy.